Juridical Analysis of Dissenting Opinions of Constitutional Judges in Constitutional Court Decisions (Universitas Negeri Semarang, 2022)
This research will raise the issue that will be studied is, First, the regulation of dissenting opinion in the Constitutional Court's Event Law. Second, the legal power of dissenting opinion in the Constitutional Court Decision. Third, the legal implications of dissenting opinion in the Constitutional Court Decision. This resulted in the conclusion First, the arrangement of dissenting opinions in the constitutional court's guidelines in this case in the FMD cannot be found as a whole. The arrangement of dissenting opinion in the PMK independence of constitutional judges in conveying their opinions is still maintained. Second, explicitly, there is no setting on dissenting opinion. The phrase used in Law No. 24 of 2003 concerning the Constitutional Court is